Enhancing Employee Psychological Well-Being through Flexible Work Arrangements: The Mediating Role of Employee Engagement - Ratih Anggraini; Signorita Signorita; Dhita Hafizha Asri (goodwood publishing, 2026)
Purpose: This study explores how flexible work arrangements influence the mental well-being of Generation Z employees and examines employee engagement as a mediating factor in this relationship. Methodology: A quantitative approach was applied in this study, targeting Generation Z employees working in Information Technology (IT) roles within manufacturing companies in Batam, Indonesia. Data were collected through an online questionnaire administered via Google Forms from November 2024 to January 2025 using a five-point Likert scale. A purposive sampling technique was applied, resulting in 200 valid responses being obtained. The collected data were examined using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Results: The analysis revealed that flexible work arrangements positively contributed to employee engagement and psychological well-being. Furthermore, employee engagement positively affects psychological well-being and serves as an intermediary variable between flexible work arrangements and employee psychological well-being. Conclusions: Flexible work arrangements significantly enhance employees’ psychological well-being, both directly and indirectly, through increased employee engagement among Generation Z employees. Work flexibility allows employees to experience higher motivation, stronger involvement, and better psychological health. Limitations: This study is limited to Generation Z employees working in IT-related roles within manufacturing companies in Batam. Therefore, the findings may not fully represent employees from other industries or generational groups. Contributions: The findings contribute to the literature on human resource management and organizational behavior by highlighting how employee engagement helps explain the connection between flexible work arrangements and psychological well-being among Generation Z employees in digital workplaces.